Rupiah Meleleh Kualitas Kredit Potensi Memburuk, Bagaimana Pelayanan Bank? - Erin Elinda Tanjung; Ruvia; Intan Maharni (PENG: Jurnal Ekonomi dan Manajemen, 2024)
The depreciation of the rupiah against foreign currencies has a significant impact on Indonesia's economy, particularly on the banking sector. Deteriorating credit quality becomes one of the main risks banks must face. This article discusses how banks can maintain their service quality amidst the potential worsening of credit quality due to the weakening of the rupiah. The methodology used is a literature review and case studies from several major banks in Indonesia. The main findings indicate that banks must implement credit risk mitigation strategies and innovations in service to maintain customer trust.